PROBLEMS OF APPLYING TECHNOLOGIES OF EDUCATION IN THE SYSTEM OF CONTINUING EDUCATION - Ubaydullaeva, Vasila (Science technology&Digital finance, 2023)
This article discusses the problems of using educational technologies, in particular, collaborative learning technologies, and outlines opinions on this issue.